A bilayer conducting polymer structure for planar perovskite solar cells with over 1,400 hours operational stability at elevated temperatures - Zhao, Yicheng; Heumueller, Thomas; Zhang, Jiyun; Luo, Junsheng; Kasian, Olga; Langner, Stefan; Kupfer, Christian; Liu, Bowen; Zhong, Yu; Elia, Jack; Osvet, Andres; Wu, Jianchang; et al. (Nature Energy, 2021)
The long-term stability of perovskite solar cells remains a challenge. Both the perovskite layer and the device architecture need to endure long-term operation. Here we first use a self-constructed high-throughput screening platform to find perovskite compositions stable under heat and light. Then, we use the most stable perovskite composition to investigate the stability of contact layers in solar cells. We report on the thermal degradation mechanism of transition metal oxide contact (for example, Ta-WOx/NiOx) and propose a bilayer structure consisting of acid-doped polymer stacked on dopant-free polymer as an alternative. The dopant-free polymer provides an acid barrier between the perovskite and the acid-doped polymer. The bilayer structure exhibits stable ohmic contact at elevated temperatures and buffers iodine vapours. The unencapsulated device based on the bilayer contact (with a MgF2 capping layer) retains 99% of its peak efficiency after 1,450 h of continuous operation at 65 degrees C in a N-2 atmosphere under metal-halide lamps. The device also shows negligible hysteresis during the entire ageing period.
CRIS-Team WoS Importer:2021-12-24

Electrospun Iridium-Based Nanofiber Catalysts for Oxygen Evolution Reaction: Influence of Calcination on Activity-Stability Relation - Kovács, Miklós; Fritsch, Birk; Lahn, Leopold; Bachmann, Julien; Kasian, Olga; Mayrhofer, Karl; Hutzler, Andreas; Dworschak, Dominik (ACS Applied Materials and Interfaces, 2024)
The enhanced utilization of noble metal catalysts through highly porous nanostructures is crucial to advancing the commercialization prospects of proton exchange membrane water electrolysis (PEMWE). In this study, hierarchically structured IrOx-based nanofiber catalyst materials for acidic water electrolysis are synthesized by electrospinning, a process known for its scalability and ease of operation. A calcination study at various temperatures from 400 to 800 °C is employed to find the best candidates for both electrocatalytic activity and stability. Morphology, structure, phase, and chemical composition are investigated using a scale-bridging approach by SEM, TEM, XRD, and XPS to shed light on the structure-function relationship of the thermally prepared nanofibers. Activity and stability are monitored by a scanning flow cell (SFC) coupled with an inductively coupled plasma mass spectrometer (ICP-MS). We evaluate the dissolution of all metals potentially incorporated into the final catalyst material throughout the synthesis pathway. Despite the opposite trend of performance and stability, the present study demonstrates that an optimum between these two aspects can be achieved at 600 °C, exhibiting values that are 1.4 and 2.4 times higher than those of the commercial reference material, respectively. The dissolution of metal contaminations such as Ni, Fe, and Cr remains minimal, exhibiting no correlation with the steps of the electrochemical protocol applied, thus exerting a negligible influence on the stability of the nanofibrous catalyst materials. This work demonstrates the scalability of electrospinning to produce nanofibers with enhanced catalyst utilization and their testing by SFC-ICP-MS. Moreover, it illustrates the influence of calcination temperature on the structure and chemical composition of the nanofibers, resulting in outstanding electrocatalytic performance and stability compared to commercial catalyst materials for PEMWE.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Acidic water electrolysis; Catalyst morphology; Electrospinning; Enhanced catalyst utilization; Iridium oxide; Temperature-controlled synthesis

Fully printed flexible perovskite solar modules with improved energy alignment by tin oxide surface modification - Dong, Lirong; Qiu, Shudi; García Cerrillo, José; Wagner, Michael; Kasian, Olga; Feroze, Sarmad; Jang, Dongju; Li, Chaohui; Le Corre, Vincent Marc; Zhang, Kaicheng; Peisert, Heiko; U. Kosasih, Felix; et al. (Energy and Environmental Science, 2024)
Fully printed flexible perovskite solar cells (f-PSCs) show great potential for the commercialization of perovskite photovoltaics owing to their compatibility with high-throughput roll-to-roll (R2R) production. However, the challenge remains in the deficiency in controlling interfacial recombination losses of the functional layer, causing remarkable loss of power conversion efficiency (PCE) in industrial production. Here, a fullerene-substituted alkylphosphonic acid dipole layer is introduced between the R2R-printed tin oxide electron transport layer and the perovskite active layer to reduce the energetic barrier and to suppress surface recombination at the buried interface. The resulting f-PSCs exhibit a PCE of 17.0% with negligible hysteresis, retain 95% of their initial PCE over 3000 bending cycles and achieve a T95 lifetime of 1200 h under 1 sun and 65 °C in nitrogen atmosphere. Moreover, the fully printed flexible perovskite solar mini-modules (f-PSMs) with a 20.25 cm2 aperture area achieve a PCE of 11.6%. The encapsulated f-PSMs retain 90% of their initial PCE after 500 h damp-heat testing at 65 °C and 85% relative humidity (ISOS-D3). This work marks an important progress toward the realization of efficient and stable flexible perovskite photovoltaics for commercialization.
CRIS-Team Scopus Importer:2024-08-16

Integrated System Built for Small-Molecule Semiconductors via High-Throughput Approaches - Wu, Jianchang; Zhang, Jiyun; Hu, Manman; Reiser, Patrick; Torresi, Luca; Friederich, Pascal; Lahn, Leopold; Kasian, Olga; Guldi, Dirk Michael; Perez-Ojeda Rodriguez, Maria Eugenia; Barabash, Anastasia; Rocha Ortiz, Juan Sebastian; et al. (Journal of the American Chemical Society, 2023)
High-throughput synthesis of solution-processable structurally variable small-molecule semiconductors is both an opportunity and a challenge. A large number of diverse molecules provide a possibility for quick material discovery and machine learning based on experimental data. However, the diversity of the molecular structure leads to the complexity of molecular properties, such as solubility, polarity, and crystallinity, which poses great challenges to solution processing and purification. Here, we first report an integrated system for the high-throughput synthesis, purification, and characterization of molecules with a large variety. Based on the principle “Like dissolves like,” we combine theoretical calculations and a robotic platform to accelerate the purification of those molecules. With this platform, a material library containing 125 molecules and their optical-electronic properties was built within a timeframe of weeks. More importantly, the high repeatability of recrystallization we design is a reliable approach to further upgrading and industrial production.<br

Lithium-Directed Transformation of Amorphous Iridium (Oxy)hydroxides To Produce Active Water Oxidation Catalysts - Esquius, Jonathan Ruiz; Morgan, David J.; Siller, Gerardo Algara; Gianolio, Diego; Aramini, Matteo; Lahn, Leopold; Kasian, Olga; Kondrat, Simon A.; Schloegl, Robert; Hutchings, Graham J.; Arrigo, Rosa; Freakley, Simon J. (Journal of the American Chemical Society, 2022)
The oxygen evolution reaction (OER) is crucial to future energy systems based on water electrolysis. Iridium oxides are promising catalysts due to their resistance to corrosion under acidic and oxidizing conditions. Highly active iridium (oxy)hydroxides prepared using alkali metal bases transform into low activity rutile IrO2 at elevated temperatures (>350 °C) during catalyst/electrode preparation. Depending on the residual amount of alkali metals, we now show that this transformation can result in either rutile IrO2 or nano-crystalline Li-intercalated IrOx. While the transition to rutile results in poor activity, the Li-intercalated IrOx has comparative activity and improved stability when compared to the highly active amorphous material despite being treated at 500 °C. This highly active nanocrystalline form of lithium iridate could be more resistant to industrial procedures to produce PEM membranes and provide a route to stabilize the high populations of redox active sites of amorphous iridium (oxy)hydroxides.
CRIS-Team Scopus Importer:2023-03-29

Low Ti Additions to Stabilize Ru-Ir Electrocatalysts for the Oxygen Evolution Reaction - Lahn, Leopold; Mingers, Andrea M.; Savan, Alan; Ludwig, Alfred; Kasian, Olga (ChemElectroChem, 2023)
Anodic oxygen evolution reaction (OER) challenges large scale application of proton exchange membrane water electrolyzers (PEMWE) due to sluggish kinetics, high overpotential and extremely corrosive environment. While Ir oxides currently provide the best balance between activity and stability, the scarcity of Ir and corresponding high market price lead to poor cost-benefit factors. Mixing Ir with more stable non-precious Ti reduces the noble metal loading and may implicate stabilization, while addition of more catalytically active Ru ensures a high reaction rate. Here, we examine the activity-stability behavior of Ru-Ir-Ti thin film material libraries with low Ti-content under the OER conditions. The high sensitivity to the dissolution of the individual alloy components was achieved by using online and off-line inductively coupled plasma mass spectrometry (ICP-MS) analysis. Our data reveal that even low Ti additions improve the stability of Ru-Ir catalysts without sacrificing activity. In particular, 5 at. % of Ti enable stability increase of Ir in the Ru-Ir catalyst by a factor of 3. Moreover, this catalyst exhibits higher activity compared to the Ti-free Ru-Ir alloys with similar Ir content. Observed activity-stability trends are discussed in light of X-ray photoelectron spectroscopy data.
Created from Fastlane, Scopus look-up
Keywords: catalyst stability; online ICP-MS; oxygen evolution reaction; Ru-Ir-Ti alloy; thin film catalyst

Simplifying contact-layer design for high-throughput printing of flexible perovskite photovoltaics - Dong, Lirong; Qiu, Shudi; Feroze, Sarmad; Wagner, Michael; Kasian, Olga; Peisert, Heiko; Kosasih, Felix U.; Ducati, Caterina; García Cerrillo, José; Tian, Jingjing; Li, Chaohui; Jang, Dongju; et al. (Energy and Environmental Science, 2024)
The realization of scalable roll-to-roll production processes for metal-halide perovskite modules is a necessary development for transferring developments and technologies from the lab to the fab. Before that, it is imperative to close the efficiency gap not only between the devices fabricated on rigid substrates versus flexible substrates, but also between solar cells to solar modules. In this regard, a critical assessment of device architectures that are more compatible to scalable fabrication is needed. Obviously, the adaption to mass manufacturing must not negatively impact device performance and operational stability. Here, by investigating the properties of printed fullerene-based phosphonic acid dipole interface layers, we establish simplified self-assembled monolayer (SAM) based n-i-p architectures without any charge extraction layers other than SAMs, which are easily processed and are thus ideally suited for mass production. We show that a contact-layer design with a printed fullerene-based SAM that has phosphonic acid is sufficient to provide good charge selectivity and to minimize interface recombination at the bottom electrode. We further show that the same SAM molecule can be used as a p-type interface material on top of the perovskite. This simplified contact-layer design, which is based on one material for both hole and electron work-function adaption is successfully integrated into our fully printed module process comprising the deposition of a carbon top electrode. The achieved open-circuit voltage exceeds 1.1 V, and the fill factor surpasses 70%, highlighting the potential of this novel interface design concept for both rigid and flexible substrates.
CRIS-Team Scopus Importer:2024-09-06